AKOMODASI KOMUNIKASI ANTAR BUDAYA PAPUA DENGAN MELAYU DI LINGKUNGAN MAHASISWA UNIVERSITAS RIAU - Wardyan Ihzan; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Cultural diversity greatly influences the way a person interacts. When interacting with people who have different cultures, a person will bring character to their culture. Among the many immigrant tribes in the area, it is the relationship between the Akit and the Malays that is most striking compared to other immigrant tribes. This happens because the people of the Akit Tribe and the Malay Tribe live next door, which makes the two tribes inevitably interact with each other. Phenomena and realities that occur in the Akit and Malay tribes today are still debating and conflicting which results in their disharmony relationship. However, communication between the immigrant ethnic community and the Akit Tribe cannot be avoided because in daily life because the two tribes need each other. This research uses Face Negotiation Theory.The purpose of this study was to determine the form of facework and conflict management of the Akit Tribe and the Malay community in Kepau Baru Village, Meranti Islands Regency.This research uses descriptive qualitative research methods. The data collection technique is done by interview, observation, and documentation. Meanwhile, the data analysis technique uses descriptive analysis according to Huberman and Miles. And the data validity checking techniques used in this study were participation extension and triangulation.The results showed that in communicating, the Akit tribe and the Malayu community displayed their positive and negative faces. The Malay community displays their positive faces by being polite. Meanwhile, the Akit people show their positive faces by showing that they are people who behave as they are. A negative face is shown by the Akit tribe and the Malay community to maintain their culture. When the two communities communicate, if they find things that are not in accordance with their culture, they will avoid and act indifferent. Prejudice and stereotypes are the causes of conflict between the Akit tribe and the Malayu community in Kepau Baru Village. In resolving conflict, the leader has a very important role, namely by way of conflict prevention, conflict resolution, conflict management, conflict resolution and conflict transformation.